Personality of karate competitors due to their sport specialization - Piepiora, P.; Petre, L.; Witkowski, K. (Archives of Budo, 2021)
Background and Study Aim: Karate competitions take place in the kata and kumite competitions. Karate athletes, depending on their preferences in the training process, focus on specializing in kata or kumite. Karate shapes the personality of practitioners. Therefore, the purpose of this work was to answer the question: whether the personality of athletes with different sports specialization is identical (similar).